Tissue‐ and cell‐expression of druggable host proteins provide insights into repurposing drugs for COVID‐19 - Jiapeng Li; Yanling Xue; Xinwen Wang; Logan S. Smith; Bing He; Shuhan Liu; Hao‐Jie Zhu (Wiley, 2022)
Abstract Several human host proteins play important roles in the lifecycle of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Many drugs targeting these host proteins have been investigated as potential therapeutics for coronavirus disease 2019 (COVID‐19). The tissue‐specific expressions of selected host proteins were summarized using proteomics data retrieved from the Human Protein Atlas, ProteomicsDB, Human Proteome Map databases, and a clinical COVID‐19 study. Protein expression features in different cell lines were summarized based on recent proteomics studies. The half‐maximal effective concentration or half‐maximal inhibitory concentration values were collected from in vitro studies. The pharmacokinetic data were mainly from studies in healthy subjects or non‐COVID‐19 patients. Considerable tissue‐specific expression patterns were observed for several host proteins. ACE2 expression in the lungs was significantly lower than in many other tissues (e.g., the kidneys and intestines); TMPRSS2 expression in the lungs was significantly lower than in other tissues (e.g., the prostate and intestines). The expression levels of endocytosis‐associated proteins CTSL, CLTC, NPC1, and PIKfyve in the lungs were comparable to or higher than most other tissues. TMPRSS2 expression was markedly different between cell lines, which could be associated with the cell‐dependent antiviral activities of several drugs. Drug delivery receptor ICAM1 and CTSB were expressed at a higher level in the lungs than in other tissues. In conclusion, the cell‐ and tissue‐specific proteomics data could help interpret the in vitro antiviral activities of host‐directed drugs in various cells and aid the transition of the in vitro findings to clinical research to develop safe and effective therapeutics for COVID‐19.